2015
DOI: 10.1517/17425255.2016.1121381
|View full text |Cite
|
Sign up to set email alerts
|

The pregnane X receptor in tuberculosis therapeutics

Abstract: Introduction Among the infectious diseases, tuberculosis (TB) remains the second cause of death after HIV. TB treatment requires the combination of multiple drugs including the rifamycin class. However, rifamycins are activators of human pregnane X receptor (PXR), a transcription factor that regulates drug metabolism, drug resistance, energy metabolism, and immune response. Rifamycin-mediated PXR activation may affect the outcome of TB therapy. Areas covered This review describes the role of PXR in modulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 130 publications
(148 reference statements)
0
10
0
1
Order By: Relevance
“…In a subsequent study, the same research group showed that PXR can modulate macrophage drug-efflux transporter expression and activity, compromising the effect of rifampicin in vitro in hMDMs (Fig 2) [92]. Previous studies showed that rifampicin is a potent PXR activator that can induce expression of important metabolizing enzymes [93]. In mice infected with M.tb, the PXR antagonist ketoconazole rescued the activity of rifampicin [92].…”
Section: Pxrmentioning
confidence: 88%
See 1 more Smart Citation
“…In a subsequent study, the same research group showed that PXR can modulate macrophage drug-efflux transporter expression and activity, compromising the effect of rifampicin in vitro in hMDMs (Fig 2) [92]. Previous studies showed that rifampicin is a potent PXR activator that can induce expression of important metabolizing enzymes [93]. In mice infected with M.tb, the PXR antagonist ketoconazole rescued the activity of rifampicin [92].…”
Section: Pxrmentioning
confidence: 88%
“…Other rifamycin derivatives such as rifapentine and rifabutin do not stimulate PXR regulation of metabolizing enzymes to the same extent as rifampicin [93], and could potentially be used as an alternative to combat PXR-mediated drug non-responsiveness. Further, rifalazil does not induce metabolizing enzymes and no effect on PXR has been observed in animal models [94].…”
Section: Pxrmentioning
confidence: 99%
“…22 PXR has many effects during the treatment of TB as its activation regulates drug metabolizing enzymes and transporters, and this effect has been associated with RIF use. 23 Although Mbatchi and colleagues 24 found no effect of variants in PXR gene on INH exposure, PXR-induced CYPmediated metabolism has been described.…”
Section: Discussionmentioning
confidence: 98%
“…The coadministration of EFV, known to affect RIF and INH exposure, may partially explain this discrepancy as almost all previous studies were conducted in TB mono‐infected subjects: the only study conducted in 56 patients coinfected with HIV/TB reported the effect of SLCO1B1 SNP on RIF concentrations at 2.5 hours, but 95% of enrolled individuals had less common genetic variants . PXR has many effects during the treatment of TB as its activation regulates drug metabolizing enzymes and transporters, and this effect has been associated with RIF use . Although Mbatchi and colleagues found no effect of variants in PXR gene on INH exposure, PXR‐induced CYP‐mediated metabolism has been described.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a balance between PXR transcriptional activation and repression is needed, not only to maintain appropriate physiologic levels of endogenous chemicals but also to achieve optimal therapeutic efficacy with fewer drug‐induced toxicities. Because of its important role in regulating drug efficacy and drug toxicity, as well as its emerging roles in other physiologic and pathologic processes such as energy metabolism and metabolic diseases, infectious diseases, cancer, and inflammatory bowel disease (IBD), as briefly discussed in Sections to , PXR has become an attractive therapeutic target . However, PXR is notorious for promiscuously binding structurally diverse chemicals, including clinical drugs, environmental toxins, and endogenous metabolites, making it a challenging therapeutic target partly because of the perceived difficulty of studying its structure‐activity relationship .…”
Section: Introductionmentioning
confidence: 99%